Moving Towards Sustainability: Environmental Management Strategies and Sustainable Infrastructures Development at Universidad Catolica de Córdoba (UCC) - Perfumo, Maria Soledad; Ferraresi, Leonela; Imhof, Lelia (Universitas Diponegoro, 2024)
This study focuses on the